Visual Image of the City and Urban Communication by Means of Public Art: Russian Experience / Визуальный облик города и городская коммуникация средствами паблик-арта: российский опыт - KARTSEVA EKATERINA A. / КАРЦЕВА Е.А. (Наука телевидения)
This paper examines the dynamics of public art in Russia, explores the diversity of contemporary art forms beyond exhibition halls, and analyses the impact of public art on the image of “central” and “peripheral” areas, as well as on its role in urban communications between the main groups of interested parties. A review of various Russian studies provides an interdisciplinary look into the subject of public art and its evolution over time from a rather narrow definition to a wide variety of interpretations implying many new issues and concepts. Researchers attribute the increasing popularity of this artistic strategy to a combination of multidirectional factors, including the growing interest among municipal and regional authorities in public art as a driving force of territory development; a rising number of curatorial projects aimed at interacting with space and environment in the context of the festival and biennial movement and art residencies; the emergence of grassroots art organizations and initiatives as modes of making artistic or public statements. Remarkable progress in digital technologies prompted attention to the creative potential of digital forms in public art, which open up new possibilities for interaction at the interface of objective and virtual reality. Some of the conclusions suggest that further development of public art presupposes more attention to its social nature and the ability to create social ties through a polylogue between different groups of city dwellers. To encourage the development of urban art based on the principles of social justice, Russia needs to foster a culture of participation as opposed to social atomization. The creation of professional organizations, legitimization and support of grassroots initiatives and artistic self-organizations may prepare the groundwork for this process. В статье рассматривается динамика паблик-арта в России как многообразия форм существования современного искусства за пределами выставочных залов и его влияния на облик как «центральных», так и удаленных от условного центра районов — на «периферии», а также осуществления с его помощью городской коммуникации между основными интересантами. Обзор работ российских исследователей дает междисциплинарный взгляд на данный термин, его эволюцию от узкого определения к вееру интерпретаций, привносящих множество новых проблем и концепций. Авторы объясняют возрастающую популярность этой художественной стратегии совокупностью разнонаправленных факторов, среди которых — рост интереса областных и муниципальных властей к паблик-арту в качестве инструмента территориального развития; увеличение кураторских инициатив, ориентированных на работу с пространством в рамках фестивального движения; формирование самоорганизаций и низовых арт-инициатив как способов художественного или общественного высказывания. Внимание уделяется и потенциалу цифровых форм паблик-арта, открывающих новые возможности для взаимодействия на пересечении объективной и виртуальной реальностей. Среди выводов статьи содержится наблюдение, что продуктивное развитие паблик-арта подразумевает большее внимание к его социальной природе, способности конструирования общественных связей посредством полилога между разными группами горожан. Для формирования городского искусства, основывающегося на принципах социальной справедливости, необходимо развитие в России культуры соучастия в противовес социальной атомизированности, чему может поспособствовать создание профессиональных организаций, легитимизация и поддержка низовых инициатив и художественных самоорганизаций.